The origins of food: The not so American Hamburger - Khoury, Colin K.; Valiño, Álvaro; Nowakowski, Kelsey (2019)
Hamburgers are an American favorite, but the origins of this meal's common ingredients are as diverse as the U.S. population. The meat patties were first served in Hamburg, Germany, and appeared on menus in New York City as early as the 1870s thanks to German immigrants.